Erratum - Efficacy of Intra-vitreal Bevacizumab for Resolution of Macular Edema Secondary to Central Retinal Vein Occlusion: Erratum - , Muhammad Younis Tahir, Afshan Ali (Pakistan Journal of Ophthalmology, 2015)
Pak J Ophthalmol 2015, Vol. 31 No. 2, on page 95. The Sequence of authors was mistaken changed. The Correct Sequence is as follows Author’s Affiliation Dr. Afshan Ali Ophthalmology Department Medical Officer Mayo Hospital, Lahore Dr. Muhammad Younis Tahir Fellowship in Vitreo-Retina Assistant Professor Ophthalmology Department BVH / Qamc, Bahawalpur